Ag-TiO2 for Efficient Methylene Blue Photodegradation Under Visible Light Irradiation - Widiyandari, Hendri; Nashir, Muhammad; Parasdila, Hanaiyah; Almas, Khanza Fadhilah; Suryana, Risa (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Photocatalysis is one of the environmentally friendly methods for degrading down wastewater contamination. TiO2 as one of the photocatalyst material is claimed can enhance the photocatalytic activity much better, if the band gap energy is reduced. In order to reduce the bandgap energy of TiO2, the novel in this research is that the temperature variations over a 24-hour period at 100 °C, 120 °C, 140 °C, and 160 °C in hydrothermal process to synthesize the photocatalyst material with Ag-doped. Diffraction patterns of Ag-TiO2 show that all sample have tetragonal crystal structure and an anatase phase which also has excellent crystallinity. Some of the nanoparticles on the surface of Ag-TiO2 have a consistent morphology, while other particles are formed irregularly. According to the DRS UV-Vis result, bandgap energy reduced as temperature increased (Eg = 3.2 eV to 2.32 eV). The results from PL Ag-TiO2 160 have the lowest intensity, which indicates a low rate of electron-hole recombination. The Ag-TiO2 160 sample produced the best photocatalytic activity, according to the results of the MB degradation test, with a relative change in concentration of 92.98% for 2 h under visible light. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).